Biodegradable behavior of coconut husk (coir) fiber reinforced starch bio-composite - Mohd Madzuan, Abdullah (2010)
In this work, a starch-based biopolymer was reinforced with coir fiber. The purpose of this research was to investigate a production of bio-composite based on different content percentage of coir fiber as a reinforcement material. Five compositions of the bio-composites were formulated containing 0%, 5%, 10%, 15% and 20% of coir fiber where 0% of fiber acts as the control sample. Coir fiber and starch were a good material for bio-composite production because there were readily biodegradable, renewable resource and low cost price. Characteristics of the bio-composite were evaluated by tensile strength, microstructure, chemical, physical and biodegradability properties. The evaluation of the mechanical properties gave a significant increase of the strength of the bio-composite with the percentage of coir fiber. The optimum value of mechanical strength was obtained at 15% fiber reinforcement and it also proved from Scanning Electron Microscope analysis where the structure of 15% fiber reinforcement showed a good interaction between coir fiber and matrix phase and coir fiber was seen well embedded in the matrix. Roughly, Fourier Transform Infrared Spectroscopy results showed the O-H peak become broader with the increment of the fiber reinforcement. The Differential Scanning Calorimetry result showed that the melting temperature was increase as the fiber composition in bio-composite was increased. In biodegradability test, it showed that when the fiber content was increase, the Aspergillus Niger was more difficult to growth and also difficult to degrade in soil. It was proven that the coir fiber reinforcement can improve the bio-composite’s durability to degrade. Averagely, the best performance of bio-composite was at 15% of coir fiber with respect to chemical bonds, dispersion and agglomeration, heat resistance, biodegradability behavior, and mechanical properties